NMR-based metabonomics study of sub-acute hepatotoxicity induced by silica nanoparticles in rats after intranasal exposure - Parveen, A.; Rizvi, S. H. M.; Gupta, A.; Singh, R.; Ahmad, I.; Mahdi, F.; Mahdi, A. A. (Cellular and Molecular Biology, 2012)
Silica nanoparticles (SiO2 NPs) are widely used commercially; however, their potential toxicity on human health has attracted particular attention. In the present study, the intranasal toxicological effect of 10nm and 80nm SiO2 NPs (dosed at 150µg for 90 days) on rats was investigated using conventional approaches and metabonomics analysis of serum. Oxidative stress was measured by assessing Lipid peroxide (LPO) levels and enzymatic activities of Superoxide dismutase (SOD), Catalase (CAT), and Glutathione (GSH) levels in liver tissue homogenate. These biochemical observations were supplemented by histological examination of liver sections. SiO2 NPs enhanced lipid peroxidation with concomitant reduction in SOD, CAT, and GSH content. In addition, SiO2 NPs also produced alterations in hepatic histopathology. We also evaluated the effect of SiO2 NPs on the activities of hepatic enzymes such as aminotransferases (ALT/AST) and alkaline phosphatase (ALP) which revealed significant increase in their activity when compared with control. Metabonomic profile of 90 days SiO2 NPs treated rat sera exhibited significant increase in lactate, alanine, acetate, creatine and choline coupled with a considerable decrease in glucose level. These perturbations, on the whole, implicate impairment in tricarboxylic acid cycle and liver metabolism, which suggests that silica nanoparticles may have a potential to induce hepatotoxicity in rats.